2017
DOI: 10.4103/ijccm.ijccm_341_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of doripenem, meropenem, and imipenem against respiratory isolates of Pseudomonas aeroginosa in a tertiary care hospital of north India

Abstract: Objective:Pseudomonas aeruginosa is one of the leading pathogen causing healthcare-associated infections, particularly in immunocompromised and critically ill patients. The development of carbapenem resistance in P. aeruginosa infections is worrisome. Data specifically comparing the susceptibility of the three available carbapenems are lacking in the Indian subcontinent.Materials and Methods:We evaluated the minimum inhibitory concentrations (MICs) of the three commonly used carbapenems– imipenem, meropenem, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
5
3
0
Order By: Relevance
“…MIC values of imipenem and meropenem drugs against MDR P. aeruginosa isolates ranged from 8μg/mL to ≥32μg/mL. Our results are consistent with an earlier study in which the MIC of all three carbapenems was >32μg/mL while the MIC of meropenem was 16μg/mL which was greater than MIC of both imipenem (4μg/mL) and doripenem (2μg/mL) (Negi et al, 2017). 63% of carbapenemase producing p. aeruginosa among MDRresistant isolates.…”
Section: Discussionsupporting
confidence: 89%
“…MIC values of imipenem and meropenem drugs against MDR P. aeruginosa isolates ranged from 8μg/mL to ≥32μg/mL. Our results are consistent with an earlier study in which the MIC of all three carbapenems was >32μg/mL while the MIC of meropenem was 16μg/mL which was greater than MIC of both imipenem (4μg/mL) and doripenem (2μg/mL) (Negi et al, 2017). 63% of carbapenemase producing p. aeruginosa among MDRresistant isolates.…”
Section: Discussionsupporting
confidence: 89%
“…Kaur, et al [20]also reported a considerable resistance of E. coli and K. pneumoniae to carbapenems drugs. The high resistance profile of bacterial organisms to meropenem as discovered in this study is also reported byLuyt, et al [34]; Negi, et al [30]; Bhatia,et al [35]. The presence of carbapenems-resistant organisms in drinking water sources poses health risk to the users.…”
Section: Resultssupporting
confidence: 83%
“…Also, resistance to meropenem and doripenem was observed among the multiple-resistant Escherichiacoli and Klebsiellapneumoniae. This resistance to doripenem and meropenem was reported by Negi, et al [30]. The resistance observed in the organisms could probably be as a result of the three fundamental mechanisms of antimicrobial resistance which are enzymatic degradation of antibacterial drugs, alteration of bacterial proteins that are antimicrobial targets, and changes in membrane permeability to antibiotics [31].…”
Section: Resultssupporting
confidence: 60%
“…Pseudomonas aeruginosa (PA) is a non-fermenter Gram-negative bacilli, which is one of the most common pathogens associated with nosocomial infections [1]. Carbapenems are commonly used for nosocomial infections, caused by Gram-negative pathogens including PA [2]. However, carbapenemresistant Pseudomonas aeruginosa (CRPA) strains are emerging worldwide, and the rate of resistance in most countries ranges from 10% to 50% [1].…”
Section: Introductionmentioning
confidence: 99%